Supplementary Feeding (Soy Biscuits) on the Frequency of Nausea and Vomiting of Pregnant Women Experiencing Hyperemesis Gravidarum in Health Crisis Situations - Munawwarah, St.; Nanda, Kiki Riskianti; Hasriantirisna, Hasriantirisna; Yahya, Fajar Dhini (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study examines the role of soy biscuits as supplementary food in reducing the frequency and severity of nausea and vomiting in pregnant women experiencing hyperemesis gravidarum (HG) in health crises. The research explores the nutritional effectiveness of soy biscuits, their acceptability among pregnant women, and their potential as a non-pharmacological intervention in community-based maternal healthcare settings, particularly at TPMB Hj Sitti Hasrah Ibrahim. Research Design and Methodology: This study employs a systematic literature review (SLR) approach, analyzing relevant studies from peer-reviewed journals to assess the impact of protein-based nutritional interventions on HG symptoms. The research synthesizes evidence on dietary strategies, maternal nutrition, and the physiological mechanisms through which soy biscuits alleviate HG symptoms. The review also incorporates empirical data from similar interventions to evaluate their feasibility in low-resource and crisis-affected healthcare settings. Findings and Discussion: The findings indicate that soy biscuits significantly stabilize blood sugar levels, reduce gastric motility disturbances, and improve maternal food tolerance. Compared to high-carbohydrate or high-fat diets, a protein-based nutrition approach is more effective in managing nausea and vomiting in patients with HG. Additionally, soy biscuits are well-tolerated and accepted by pregnant women, making them a practical intervention for managing HG in settings with limited access to pharmacological treatments. Implications: This study offers practical insights for healthcare providers, policymakers, and food manufacturers advocating for nutritional interventions in maternal healthcare programs. Future research should investigate alternative formulations, large-scale implementation, and long-term health outcomes to establish a comprehensive dietary strategy for managing HG.